Do Financial Sector Reforms Influence Manufacturing Sector Performance in Nigeria? - Ozekhome, Hassan O.; Esan, Benson. A. (Finance & Economics Review, 2021)
Purpose: The study empirically investigates whether or not financial sector reforms influence manufacturing sector performance in Nigeria. Method: A weighted index covering the gradual progression, scope, dimensions, and institutional changes involved in the reform and regulation of the financial sector is constructed for the study. Annual time series data covering the period 1986-2020 were used for the study. Cointegration and error correction modeling techniques were utilized for the empirical analysis. Results: The empirical results show evidence of a short-run dynamic and a long-run equilibrium relationship between financial sector reforms and manufacturing sector performance in Nigeria. Specifically, financial sector reforms, credit to the private sector, electricity supply, and capacity utilization positively drive manufacturing sector performance in Nigeria. Further findings show that the exchange rate and interest rate variables are negatively and significantly related to manufacturing sector performance. Implications: Based on the empirical evidence, the continuous reforms of the financial sector are imperative to enhance its credit intermediation role to the real sector of the economy, particularly, the manufacturing sector. The provision of accessible, reliable, and stable electricity supply, as well as sound, stable and competitive macroeconomic policy environment and appropriate institutional framework are also imperative. Originality: The study is unique in the sense that it utilized a weighted index of several key dimensions of the progression and institutional changes involved in the reform of the financial sector, thereby sufficiently capturing the whole process of financial reforms in Nigeria.